Gaps in expectations and current practices of pharmacy services among doctors and patients - an exploratory study in a Sri Lankan tertiary care hospital providing free healthcare - J. A. L. Anjalee; V. Rutter; N. R. Samaranayake (BMC, 2022)
Abstract The pharmacist is an important link between doctor and patient. To optimise patient care, it is essential that expectations of doctors and patients regarding pharmacy services are met. Hence the objective of this study was to assess the satisfaction levels of doctors and patients on pharmacy services currently provided, and their expectations from pharmacy services. This cross sectional study was conducted in selected clinics of a university based teaching hospital. Questionnaires developed in-house by referring previously published resources, content validated by a group of experts, and face validated through a pilot study were used. Doctors and patients of chronic disease clinics were selected for the study. All doctors involved in prescribing for more than six months, and patients or their regular care givers attending clinics for more than one year were included. Mentally incapacitated patients were excluded. An interviewee administered questionnaire was distributed to doctors and an interviewer administered questionnaire was used for patients. Exploratory factor analysis (EFA) (principal component analysis with Varimax rotation) was conducted to divide variables of the questionnaires into reliable components. Response rate of doctors was 82.3%. Among them 59.6% (50/84) doctors said that they have a good relationship with pharmacists, and 89.3% (75/84) expected communication with pharmacists more often. EFA for doctors' perceptions resulted in four components. A statistically significant difference was observed between doctors' expectation (95.9% - 81/84) and current practice (22.6% - 19/84) on communicating medication issues (p<0.001). A total of 380 patients participated. EFA for patients' perceptions resulted in ten components. The majority considered pharmacists as an integral part of the healthcare system (98.7% - 375/380) and experts in medication (84.7% - 322/380). They further perceived that dispensed medications are safe (82.9% - 315/380) and of good quality (76.3% - 290/380). Further 95.5% (363/380) were satisfied with dispensing label information. A statistically significant difference was found between the expectations (93% - 353/380) and satisfaction levels (86.5% - 329/380) of patients on pharmacy services (p=0.003). According to findings, both doctors and patients held a positive perception on pharmacy services and pharmacists, but the statistically significant gap reported between expectations and current level of pharmacy service, highlighting both the potential and scope for service improvement.